Gluteal Region Reshaping of Massive Weight Loss Patients—A Decision-Making Strategy - Mahgoub, Mohamed Ali; Zeina, Ahmed Mahmoud; Bahaa El-Din, Ahmed Mohamed; El-Sabbagh, Ahmed Hassan; Bassetto, Franco; Vindigni, Vincenzo (Archives of Plastic Surgery, 2022)
Background Massive weight loss (MWL) is a very common presentation that you may face as a plastic surgeon. Each patient has his own individual criteria, so, you should work according to a well-organized plan, especially when such cases have concerns about their gluteal area contour that were neglected before by many surgeons. A decision-making strategy was used to give a personalized treatment for targeting gluteal region reshaping of MWL patients.Methods This study considered all patients with MWL subjected to buttock reshaping. There was no randomization in treatment; there was a case-by-case assessment. We analyzed the features of the buttocks, the type of surgery performed, the outcomes, and the complications.Results Fifty two patients were included (41 females and 11 males), ages ranged between 21 and 66 years. Demographic data, preoperative body mass index (BMI), duration of surgery, type of surgery, and postoperative complications were collected. Statistically significant improvements were observed in gluteal ptosis and patient satisfaction grades.Conclusion Aesthetic improvement of the buttocks involves either augmentation or contouring that may be obtained by liposculpture, surgical lifting, or combination. Patients with MWL have high expectations and are often treated with multiple procedures. Thus, an easy strategic approach personalized on each patient to treat multiple adjacent areas in one operation is necessary. Adipose tissue distribution, gluteal skin status, and BMI were the main factors that can forcefully affect our plan to guarantee reduction of unpleasant results and complications and improve patient satisfaction.
Keywords: massive weight loss; postbariatric surgery; belt lipectomy; liposuction